Upaya Guru Dalam Menanamkan Nilai-Nilai Religius Melalui Kegiatan Keagamaan Di MA Darut Taqwa Purwosasi - Zakiatul Fakhiro (AL-Ikhtiar : Jurnal Studi Islam, 2025)
The objectives of this study are: (1) to determine teachers' efforts in instilling religious values through religious activities in students at MA Darut Taqwa, (2) to determine the supporting and inhibiting factors faced in instilling religious values through religious activities in students at MA Darut Taqwa. This study uses a descriptive qualitative research approach. The data in this study include primary data and secondary data. Data were collected through interview techniques, observation, and documentation studies. Data analysis techniques include data reduction, data presentation, and drawing conclusions. Checking the validity of the data findings was carried out through source triangulation, time triangulation, and technical triangulation. The results of this study indicate that: 1) Madrasah Aliyah Darut Taqwa Sengonagung consistently and systematically strives to instill religious values. Teachers' efforts are realized through strong role models, routine habituation practices, providing wise advice, and caring attention and guidance. In addition, an educational punishment system is also implemented to build student awareness. 2) There are several obstacles that need to be overcome. Physical facility constraints, particularly in mosques, impact student participation in worship. Furthermore, challenges remain in fostering students' internal awareness to fully participate without external supervision. The effectiveness of punishment is also not entirely uniform in creating a long-term deterrent effect. Abstrak The objectives of this study are: (1) to determine teachers' efforts in instilling religious values through religious activities in students at MA Darut Taqwa, (2) to determine the supporting and inhibiting factors faced in instilling religious values through religious activities in students at MA Darut Taqwa. This study uses a descriptive qualitative research approach. The data in this study include primary data and secondary data. Data were collected through interview techniques, observation, and documentation studies. Data analysis techniques include data reduction, data presentation, and drawing conclusions. Checking the validity of the data findings was carried out through source triangulation, time triangulation, and technical triangulation. The results of this study indicate that: 1) Madrasah Aliyah Darut Taqwa Sengonagung consistently and systematically strives to instill religious values. Teachers' efforts are realized through strong role models, routine habituation practices, providing wise advice, and caring attention and guidance. In addition, an educational punishment system is also implemented to build student awareness. 2) There are several obstacles that need to be overcome. Physical facility constraints, particularly in mosques, impact student participation in worship. Furthermore, challenges remain in fostering students' internal awareness to fully participate without external supervision. The effectiveness of punishment is also not entirely uniform in creating a long-term deterrent effect.